Predictive Values of Risk Factors in Neonatal Sepsis (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Neonatal sepsis is one of the most important causes of mortality and morbidity especially in developing countries. Management of such cases is difficult, costly and need expert centers in many cases. Therefore, identification of the risk factors and their predictive values may help optimizing its management. With the above idea this case-control study was done to see the effects of maternal and neonatal risk factors and to find their predictive values in the development of neonatal sepsis. Fifty cases and fifty suitably matched controls were enrolled in the study and different maternal, natal and newborn factors were compared. Many risk factors were found to have influence in the development of neonatal sepsis. Among them the maternal intrapartum fever, foul smelling liquor, young mother (< 20 yrs), poor income group, prolonged labor, unclean vaginal examination (UVE) and primi mother were much associated with the occurrence of sepsis. Also the neonatal factors, like prematurity, resuscitation at birth and low APGAR score carried the significant risk of developing sepsis. But when relative influence of these risk factors were analyzed over neonatal sepsis in detecting their predictive values, it was found that irregular antenatal check up, prematurity, resuscitation at birth, and maternal intrapartum fever had influenced most in the development of neonatal sepsis in chronological order. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11324   J Bangladesh Coll Phys Surg 2011; 29: 187-195